Regional Culture and Urban Agriculturalists of Mexico City - Torres Lima, Pablo; Burns, Allan F. (Anthropologica, 2022)
This article describes two agricultural regions of Mexico City where households reproduce forms of labour organization and technological inputs around agricultural production as the result of the cultural and social intersection with an urban and rural economy. Since the structure of the regional culture is based on organizational patterns within the multigenerational family, we discuss how urban agriculture is the consolidation of cultural networks among regional space and community. We argue that the struggle to adapt to processes of change caused by urbanization has been carried out not only for technological or economic reasons pertaining to agricultural activities, but also because of the desire to defend a cultural space, a shared territory where relationships with nature and among social groups are consolidated. The urban agriculturalists of southern Mexico City see themselves neither as farmers nor as urban inhabitants, but as the unity of both in one according to the internal cultural and social requirements of their geographical space.